Chemical modification in the creation of novel biocatalysts. - Díaz-Rodríguez, A; Davis, B (2011)
Enzymes are able to perform a multitude of chemical and biochemical transformations with efficiencies that are typically unrivalled by chemical catalysts. However, these evolved systems may lack breadth or utility in other non-natural applications. Altering enzyme and protein scaffolds through covalent modification can expand the usefulness of native biocatalysts not only for synthetic application but also for therapeutic use. This review summarizes recent developments in the field of chemical modification of enzymes and how they can be applied to synthesis and biological research.